Analysis of cadets' online learning readiness at PIP Makassar - Dodik Widarbowo (ILIN Institute Makassar, 2021)
This study was designed to see the readiness of online learning of cadets at PIP Makassar during the Covid-19 period with a quantitative approach. This research uses a descriptive research method. For data processing, by grouping the data from the questionnaire/questionnaire according to the variables studied, looking for the average value in each group of research variables, determining the level of readiness for each group of variables, determining the level of readiness to apply online learning at the institutional level. The research was conducted at PIP Makassar, which was held at the end of June. The subjects in this study were 362 cadets from 3 majors in Nautika, KALK and Teknika. This study used a questionnaire containing 30 questions based on predetermined reference factors. From the results of the questionnaire, it will be assessed using a 0-2 rating scale. Dari on data obtained showed the lowest scores were entered in the category of 11-25 are six people, which indicates that the cadets must take the time and effort to prepare and adapt to online learning. While the cadets with a score of 51-60 are 92 people who show the level of readiness that is very ready for online learning, while gender does not affect online learning readiness.